Long-Term Methionine Exposure Induces Memory Impairment on Inhibitory Avoidance Task and Alters Acetylcholinesterase Activity and Expression in Zebrafish (Danio rerio) - Fernanda Cenci Vuaden (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-08-15T20:35:27Z No. of bitstreams: 2 LongTerm_Methionine_Exposure_Induces_Memory_Impairment_on_Inhibitory_Avoidance_Task_and_Alters_Acetylcholinesterase.pdf: 356157 bytes, checksum: 6a46e041cdec8e6f78df3d417be2dbc3 (MD5) LongTerm_Methionine_Exposure_Induces_Memory_Impairment_on_Inhibitory_Avoidance_Task_and_Alters_Acetylcholinesterase.pdf: 356157 bytes, checksum: 6a46e041cdec8e6f78df3d417be2dbc3 (MD5)